Modification of Hand Molding Flower Vase for Thermo Plastic Recycling - Karnova Yanel (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2021)
Broadly speaking, plastics can be grouped into two groups, namely: thermoplast plastics and thermoset plastics. Thermoplast plastics are plastics that can be repeatedly printed in the presence of heat. Thermoplast plastics include: PE (Polyethilene), PP (Polypropylene), PS (Polystirene), ABS (Abutile Butadine Styrene), Nylon, PET (Polyethilene Terephthalete), POM (Polyacetal), PC (Polycarbonate) etc. Meanwhile, thermoset plastic is plastic which, if it has undergone certain conditions, cannot be reprinted because the polymer structure is in the form of a three-dimensional network. In making flower vases using hand molding tools, there are still shortcomings, such as during the melting process of plastic material, the heat given by the oil stove has not yet maximally spread the heat to the mold which causes the results to be not optimal. Besides, the heat given by the oil stove is not yet known by the operator. , because in the manufacture of flower vases have not used a controller to determine the temperature in the hand molding tool, the old mold results in the cylinder cannot be used for tensile testing. Therefore it is necessary to modify the hand molding tool. Based on the results of testing the tools that have been done, the following conclusions can be drawn: The product has a height of 16 cm, a thickness of 4 mm, a hand-molding tool can be a solution for reducing waste in the environment, plastic can be formed into a product that is valuable by processing it according to the temperature.